Understanding the effects of green marketing management on muslim consumers in Malaysia from and Islamic perspective - Haque, A. K. M. Ahasanul; Rosli, Norhizan; Abdullah, Kalthom (2014)
The association of green marketing with Islamic marketing is still very new. This paper aims to conceptually link green marketing with Islamic marketing philosophies and to understand green marketing concept from an Islamic perspective. This study investigates whether Muslim consumers in Malaysia identify with the green marketing principals and philosophies based on their religious beliefs and understanding, particularly Islam. This is a conceptual paper. A self-administered survey questionnaire will be distributed among 150 Malaysian respondents from various demographic backgrounds, and will be analysed using SPSS program. Initial finding suggests that even though Malaysian consumers have some degree of understanding of green marketing concepts and tools, however, not many Muslim consumers could relate their religious understanding to green marketing practices. Religious understanding among Malaysian consumers could be applied in the realm of green marketing theory as the phenomenon could be observed from the consumption or purchase pattern of Muslim consumers. Although not all elements of green marketing management theory could be applied in Islamic society, however, green marketing concepts and philosophies will provide some guidelines that could be applied in advancing marketing management theory from the Islamic perspective. It was hypothesized that being a Muslim, consumers are expected to develop some form of religious belief or values based on their knowledge gained from the religious teaching of Islam. As a Muslim, consumers are expected to be more supportive of green activities (e.g., environmental protection) as this responsibility to protect the wellbeing of human and the environment has been written in the Qu’ran. This study shall propagate among the Muslim consumers in Malaysia the importance of understanding that green marketing is part and parcel of Islamic Marketing philosophy derived from Devine principals. Contrary to the hypotheses, initial findings found that Muslim consumers were less concern about protecting the environment as reflected in their responses to questions raised on green marketing concepts and tools.